2006
DOI: 10.1029/2005jc003149
|View full text |Cite
|
Sign up to set email alerts
|

Swash‐aquifer interaction in the vicinity of the water table exit point on a sandy beach

Abstract: [1] The coupling of sandy beach aquifers with the swash zone in the vicinity of the water table exit point is investigated through simultaneous measurements of the instantaneous shoreline (swash front) location, pore pressures and the water table exit point. The field observations reveal new insights into swash-aquifer coupling not previously gleaned from measurements of pore pressure only. In particular, for the case where the exit point is seaward of the observation point, the pore pressure response is corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…frictional effects, leading to a stronger penetration into the aquifer. Waves of higher frequencies, such as wave runup, are preferentially damped by the aquifer within tens of meters away from the coast (Cartwright et al, 2006). The characteristic length scale (sT/S) 0.5 describes the distance of diffusive wave propagation (Turcotte and Schubert, 2002).…”
Section: Water Level (M)mentioning
confidence: 99%
See 1 more Smart Citation
“…frictional effects, leading to a stronger penetration into the aquifer. Waves of higher frequencies, such as wave runup, are preferentially damped by the aquifer within tens of meters away from the coast (Cartwright et al, 2006). The characteristic length scale (sT/S) 0.5 describes the distance of diffusive wave propagation (Turcotte and Schubert, 2002).…”
Section: Water Level (M)mentioning
confidence: 99%
“…The interaction between runup and the groundwater table in the littoral zone is well known (e.g., Hegge and Masselink, 1991). The amplitude becomes increasingly damped inland (Li et al, 1997) and is hardly detectable farther than tens of meters away from the shoreline (Cartwright et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such quantification is not easy to handle due to the dynamic nature of these systems having a very fast response time to hydrologic change owing to their closeness to soil surface [1]. In fact, many researchers reported rapid and disproportionate water table rise in response to rainfall events observed in shallow groundwater systems [4][5][6]. They showed that shallow water tables can often rise disproportionately compared to the volume of infiltrated water.…”
Section: Introductionmentioning
confidence: 99%
“…Such disproportionate rise was observed by many researchers in a variety of shallow groundwater systems (e.g. O'Brien, 1982;Abdul and Gillham, 1984;Cartwright et al, 2006). They showed that shallow water tables can often rise disproportionately compared to the volume of infiltrated water.…”
Section: Shallow Groundwater Monitoring Systemmentioning
confidence: 97%